Adsorption enhancement of elemental mercury by various surface modified coconut husk as eco-friendly low-cost adsorbents. (April 2016) - Johari, Khairiraihanna; Saman, Norasikin; Song, Shiow Tien; Chin, Cheu Siew; Kong, Helen; Mat, Hanapi
Abstract: Coconut husk (CH), consisting of coconut pith (CP) and coconut fiber (CF) is abundant and cheap, and has the potential to be used as adsorbent for elemental mercury (Hg 0 ) removal. CP and CF surfaces were modified by mercerization and bleaching methods and characterized using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and analysis of moisture and ash. The elemental mercury adsorption measurements were carried out at the following conditions: initial Hg 0 concentration, 200 ± 20 μg/m 3 ; bed temperature, 50 ± 1 °C; N2 flow rate, 0.05 L/min; mass of adsorbent, 50 mg; and adsorbent particle size of between 75 and 100 μm. The surface morphology and surface functional groups of adsorbents significantly changed after treatments and resulted in different Hg 0 adsorption performances. The highest Hg 0 adsorption capacity was observed for CP-NaOH (956.282 ng/g), followed by CP-Pristine (730.250 ng/g), CF-NaOCl (639.948 ng/g), CF-H2 O2 (634.347 ng/g), CF-NaOH (611.678 ng/g), CF-H2 O2 (531.277 ng/g), CP-NaOCl (501.126 ng/g), and CF (431.773 ng/g). The experimental breakthrough data for all the adsorbents produced a good fit to the pseudo-second order kinetic model. Graphical abstract: Highlights: Coconut waste feasibility as Hg 0 adsorbents was confirmed. Alkali-treated CP adsorbent performed the highest adsorption capacity. Faster Hg 0 adsorption rate was observed for surface-treated adsorbents. Pseudo-second-order kinetic model best described Hg 0 adsorption behaviors.